(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today’s age, the internet has a major influence on culture. Through the use of the internet, people all over the world are connected, utilizing different platforms of technology that can access the internet. As the world continues to enhance technological resources, educational organizations worldwide also adopt the changes and developments that can bring students into a brighter future. Technology provides support in the teaching and learning process. This research aims to determine the effects of technology on the academic preparedness of the graduating students majoring in social science at Bestlink College of the Philippines. Through various studies, it is widely accepted that using technology by students has positive and negative effects on their academic performance. Some students have become addicted to technology, which has brought them into severe medical conditions. The academic preparedness of the graduating students is a vital aspect of having a successful future. Therefore, different schools worldwide apply and integrate technologies into students’ learning processes to stimulate their critical thinking skills when using technology. A normative description method was used in conducting this research. Twenty (20) graduating students of Bachelor of Secondary Education Major in Social Science to solicit on the assessment relative to effects of technology on their academic preparedness and performance. The sampling technique was simple and random, with the data collected through analysis.